Studi Eksprerimental Pengaruh Penambahan Limbah Karet terhadap Kuat Tekan Beton - Kahfi Al Fajri Muis; Asri Yuda Trinanda; Rita Nasmirayanti (Civil Engineering Collaboration, 2021)
Building strength that is not up to standard can even be a very bad thing for building users where if the strength is not sufficient then the building will collapse and even collapse if something happens, such as an earthquake and other things. Therefore, this journal aims to mix the strength of concrete with the planning standard which is the Indonesian Nasyonal Standard (SNI), and also this report is a concrete mixing that aims to help the surrounding environment regarding crumb rubber waste, can this waste be used for concrete mixes which aims to reduce the use of coarse aggregate and can increase the compressive strength of concrete, the increasing need for the use of concrete materials, is directly proportional to the increase in the basic needs of concrete constituents which are generally sourced from nature. This research was conducted at the construction materials laboratory of the Putra Indonesia University campus "YPTK" Padang, this research is a concrete mix design used is 1%, 2.5%, 5%, 10%, and in this mix planning aims to reduce the use of coarse aggregate , and the design of this concrete has a concrete treatment time with a span of 3, 7, 21, 28 days, from the results of concrete design which is more focused on the maximum concrete strength time is 28 days, the compressive strength of concrete without mixture is 19.52 Mpa and concrete with 1% concrete mixture is 21.03 Mpa, 2.5% is 13.29 Mpa, 5% is 14.52 Mpa, and 10% is 12.86 Mpa. With a sample cylinder size of 150x300 mm, from the results of this study, we can see that mixing concrete with crumb rubber waste can increase the compressive strength of concrete, but if mixing concrete with too much crumb rubber can cause the concrete to become weak and even unfit.